Frequency of Cardiac Rhythm Abnormalities in a Half Million Adults - Khurshid, Shaan; Choi, Seung Hoan; Weng, Lu-Chen; Wang, Elizabeth Y; Trinquart, Ludovic; Benjamin, Emelia J; Ellinor, Patrick T; Lubitz, Steven A (Circulation. Arrhythmia and electrophysiology, 2018)
The frequency of cardiac rhythm abnormalities and their risk factors in community-dwelling adults are not well characterized. We determined the frequency of rhythm abnormalities in the UK Biobank, a national prospective cohort. We tested associations between risk factors and incident rhythm abnormalities using multivariable proportional hazards regression. Of 502 627 adults (median age, 58 years [interquartile range, 13]; 54.4% women), 2.35% had a baseline rhythm abnormality. The prevalence increased with age with 4.84% of individuals aged 65 to 73 years affected. During 3 368 332 person-years of follow-up, 15 906 new rhythm abnormalities were detected (4.72 per 1000 person-years; 95% confidence interval [CI]: 4.65-4.80). Atrial fibrillation (3.11 per 1000 person-years; 95% CI: 3.05-3.17), bradyarrhythmias (0.89 per 1000 person-years; 95% CI: 0.86-0.92), and conduction system diseases (1.06 per 1000 person-years; 95% CI: 1.02-1.09) were more common than supraventricular (0.51 per 1000 person-years; 95% CI: 0.48-0.53) and ventricular arrhythmias (0.57 per 1000 person-years; 95% CI: 0.55-0.60). Older age (hazard ratio [HR]: 2.35 per 10-year increase; 95% CI: 2.29-2.41; <0.01), male sex (HR: 1.83; 95% CI: 1.76-1.89; <0.01), hypertension (HR: 1.49; 95% CI: 1.44-1.54; <0.01), chronic kidney disease (HR: 1.95; 95% CI: 1.67-2.27; <0.01), and heart failure (HR: 1.99; 95% CI: 1.76-2.26; <0.01) were associated with new rhythm abnormalities. The frequency of rhythm abnormalities in middle-aged to older community-dwelling adults is substantial. Atrial fibrillation, bradyarrhythmias, and conduction system diseases account for most rhythm conditions.